Trace-elemental and multi-isotopic (Sr-Nd-Pb) discrimination of jade in the circum-Caribbean: Implications for pre-colonial inter-island exchange networks. (November 2021) - Knaf, A.C.S.; Habiba; Shafie, T.; Koornneef, J.M.; Hertwig, A.; Cárdenas-Párraga, J.; García-Casco, A.; Harlow, G.E.; Schertl, H.-P.; Maresch, W.V.; López Belando, A.J.; Hofman, C.L.; et al.
Abstract: Dense and strong, hydrothermal-metasomatic jadeitite and jadeite-omphacite rocks were used as tools and adornments throughout the wider Caribbean since initial inhabitation. Regionally, rich sources of jadeitite and jadeite-omphacite jade are known only in Guatemala (north and south of the Motagua Fault Zone), eastern Cuba and the northern Dominican Republic, establishing that humans transported jadeitic material over vast distances. This study validates that geochemical fingerprinting is a viable provenance method for Caribbean pre-colonial jadeitic lithologies. An assemblage of 101 source rocks has been characterised for trace element and combined Sr-Nd-Pb isotope compositions. Four statistical approaches (Principal Component Analysis, t-Distributed Stochastic Neighbour Embedding, Decision Tree, and Multiclass Regression) were assessed, employing source-distinct trace element ratios. A multiclass regression technique based on trace element ratios of immobile high field strength, light to medium rare earth and fluid-mobile, large-ion-lithophile elements is shown to be most effective in discriminating the four source regions. Ninety-one % of the Guatemalan samples can be discriminated from the Dominican and Cuban sources using La/Th, Zr/Hf and Y/Th ratios. Jadeitic rocks cropping out in the Dominican Republic can be distinguished from Cuban jades employing Er/Yb, Nb/Ta and Ba/Rb ratios with 71% certainty. Furthermore, the two Guatemala sources, north and south of the Motagua Fault Zone, can be discriminated by using (among others) Zr/Hf, Ta/Th, La/Sm and Dy/Y ratios with an 89% success rate. This raises the possibility of determining, in detail, former trading and mobility networks between different islands and the Meso- and Central American mainland within the Greater Caribbean. The provenance technique was applied to 19 pre-colonial jade celts excavated from the Late Ceramic Age Playa Grande archaeological site in the northern Dominican Republic. Three artefacts are discriminated as derived from the Guatemalan source, indicating that, despite a source of jade within 25 km, material was traded from Guatemala. The presence of Guatemalan jade in the Playa Grande lithic assemblage provides further evidence of large scale (>3000 km), regional trading and indigenous knowledge transfer networks. Highlights: A trace element and multi-isotopic geochemical database of circum-Caribbean jade and jadeitite sources. Guatemala, Cuba and the Dominican Republic sources are geochemically discriminated by applying a binary logistic regression method. Predictive modelling of artefact provenance is viable for sources potentially exploited by pre-colonial indigenous societies. Artefacts from a Late Ceramic Age jadeitite production site in the northern Dominican Republic include Guatemalan material. Evidence of large scale (>3000 km) pre-Hispanic trade networks in the Greater Caribbean.